Double network laminarin-boronic/alginate dynamic bioink for 3D bioprinting cell-laden constructs - Amaral, Adérito J. R. (2022)
The design of dynamically crosslinked hydrogel bioinks for three-dimensional (3D) bioprinting is emerging as a valuable strategy to advance the fabrication of mechanically tuneable cell-laden constructs for 3Din vitrodisease modelling and tissue engineering applications. Herein, a dynamic bioink comprising boronic acid-functionalised laminarin and alginate is explored for bioprinting 3D constructs under physiologically relevant conditions. The formulated bioink takes advantage of a double crosslinked network that combines covalent but reversible boronate ester bonds and ionic gelation via divalent cations. Moreover, it exhibits suitable rheological properties and improved mechanical features owing to its modular crosslinking chemistry, yielding stable constructs with user-programmable architecture. We explored such dynamic bioink as a supporting matrix for different cell classes, namely osteoblast precursors, fibroblasts and breast cancer cells. The resulting cell-laden bioprinted hydrogels display a homogeneous cell distribution post-printing and exceptional cell viability (>90%) that can be maintained for prolonged time periods in culture (14 days) for all cell lines. This simple and chemically versatile approach is envisaged to accelerate the development of multifunctional bioinks and contribute towards the fabrication of biomimetic 3D scaffolds with applicability in a wide range of predictive or exploratory biomedical platforms.